Kak otec selkupskie skazki rasskazyval_Skazka pro Idju - Andrey Filchenko; Nadia Fedotova; Sergej Kovylin; A.A.Kim; N.P.Maksimova (Andrey Filchenko, 2014)
Southern Selkup, . river, text recorded in ., by researcher ., from speaker . born in . in Ozernoe village, speaker bi-lingual Selkup-Russian, education - . Archived: Tomsk TSPU Field Archive. Volume C-. pp. Manuscript scanned by J. in 2012; annotated and translated by ., in 2013. Previously .published. Автор текста (рассказчик): . Родился прим. в . г. в . Образование среднее. Жил в . Автор записи (кем записано): .: Записано в . г. в п. ., Томская область. Хранится: Архив ЯНС ТГПУ: Том C-., стр. . Манускрипт оцифрован каф. ЯНС: - сканирование: ., 2012 - набор, глосиирование и перевод: ., 2013 Ранее . публиковался. Comprehensive Documentation & Analysis of two Endangered Siberian Languages: legacy data and last speakers of Eastern Khanty and Southern Selkup Southern Selkup legacy text data. Speaker: Itkupova Ljubava Pavlovna, born 1911, in Ivankina village. Both parents - Selkup. Literate. Recorded by A.A.Kim and N.P.Maksimova, in 1981, in Ivankino village. Should be an audio recording. Manuscript scanned: Julija Kurganskaja in 2012. Transcribed and translated: Sergej Kovylin, Nadia Fedotova, Natalija Maksimova, Andrey Filchenko. Archived: Tomsk archive - V: C-58, pp.353-367. Южно селькупский текст. Автор текста (рассказчик): Иткупова Любава Павловна, 1911 г.р. Родилась в д. Иванкино. Родители - селькупы. Автор записи (кем записано): А.А. Ким и Н.П.Максимова, 1981, Иванкино. Манускрипт оцифрован каф. ЯНС: Курганская Ю.В. 2012. Набор, глоссирование и перевод: Сергей Ковылин, Надья Федотова, Наталья Максимова, Андрей Фильченко. Архив КЯНС ТГПУ, том С-58, сс.353-367. Southern Selkup birth year approximate